2004
DOI: 10.1055/s-2004-821065
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotic Use in Pediatric Burn Units

Abstract: Prophylactic antibiotic use in childhood burns is controversial. The efficiency of antibiotic prophylaxis in 77 pediatric burn patients was evaluated. Forty-seven patients received prophylactic antibiotics (Group AP), while 30 patients received no prophylaxis (Group NP). Age, wound depth, day of admission, mechanism of burn injury, type of dressings were similar for both groups (p > 0.05). Wound infection rates were 21.3 % in Group AP and 16.7 % in Group NP (p > 0.05). S. aureus, Enterobacter spp., P. aerugino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 12 publications
2
36
0
9
Order By: Relevance
“…20,21 En el estudio llevado a cabo por Ergün y cols., 22 no se demostró que la profilaxis antibiótica sistémica fuera eficaz para prevenir la infección. Por el contrario, se relacionó con mayores tasas de infección, lo que coincide con lo observado en esta serie.…”
Section: Discussionunclassified
“…20,21 En el estudio llevado a cabo por Ergün y cols., 22 no se demostró que la profilaxis antibiótica sistémica fuera eficaz para prevenir la infección. Por el contrario, se relacionó con mayores tasas de infección, lo que coincide con lo observado en esta serie.…”
Section: Discussionunclassified
“…The prevalence of MRSA is various in clinical samples of burn patients as the result of distribution of PantonValentine Leukocidin (PVL) gene of the bacteria, Staphylococcal Cassette Chromosome mec (SCCmec) types and antibiotic resistant genes of the MRSA isolates. The disruption of the normal skin barrier and the immune compromised status make burn an easy target for MRSA colonization [21]. Additionally, using various types of penicillin too much without changing and self uses of antibiotic randomly are risks for development of MRSA colonization in which supported by Branski, L.K., et al [22].…”
Section: Bacteriological Infectionsmentioning
confidence: 99%
“…This is in contrast to other studies which are shown that a Pseudomonas bacterium was the most common pathogen in pediatric burn patients. 32,62,74 The incidence of P. aeruginosa infection in the pediatric burn wards may be due to the fact that this bacterium thrives in a moist environment, and its ability to resist killing by more of antimicrobials. The minimal nutritional requirements of Pseudomonas, its ability to grow in distilled water and its tolerance to a wide variety of physical conditions in which contribute to its ecological success and ultimately to its role as an effective opportunistic pathogen.…”
mentioning
confidence: 99%